The Phenomenon of Curriculum Development Dynamics in Indonesia: Challenges, Adaptation, and Its Implications on Teacher Performance - Mursidi; Tolkhah Khuriza; Nurul Mubin (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
Curriculum development and change are inevitable in the education system to meet the demands of the times. However, for teachers who stand in front of their classrooms every morning, curriculum change is like a tectonic earthquake. There's a classic adage often heard cynically in the teachers' lounge: "Change the minister, change the curriculum." This statement reflects fatigue, confusion, and the historical reality of our education system. However, on the other hand, we are also faced with an undeniable fact: the world is changing very rapidly. The Industrial Revolution 4.0, artificial intelligence, and global dynamics demand new competencies from the next generation. The curriculum, as the compass of education, inevitably must be recalibrated. This article examines the phenomenon of dynamic curriculum development in Indonesia, focusing on the challenges faced by teachers, the adaptation process, and its implications for the quality of learning. Based on a literature review and analysis of socio-educational phenomena, it was found that dynamic curriculum changes often create administrative and psychological burdens for teachers in the initial phase. However, with systemic support such as training, learning communities, and educational technology platforms, teachers can transform into more adaptive learning facilitators. This paper concludes that the success of curriculum change depends heavily on teacher readiness and support from the government and the school ecosystem.